PUBLIC OPINION ABOUT THE PERSONALITY AS CRITERION OF DEFINITION OF DISCIPLINARY MEASURES ON COMMON LAW OF THE SIBERIAN NOMADS - Naumkina V. V. (Scientific Journal of Pedagogy and Economics, 2019)
Practice of activity of the courts of verbal punishment on the basis of norms of common law is studied. The purpose of work is the analysis identification of influence of reputation on the decision of judicial authorities. A subject of article are norms of common law and traditional views of the Siberian nomads. With application of a historical and legal method and synthesis influence of public opinion and reputation on the judgment of verbal punishment and works of scientists-lawyers is investigated. The reputation of the person consisted of two components: the attitude of society towards family which part is the personality and reputation of the individual. The reputation of the person was considered by bodies as the proof of guilt or not guilt, truthfulness of indications and other. The author marks out criteria of determination of the status of family and the status of the personality in criminal law. At decision-making the reputation of all participants of process was considered.